2016 IEEE 13th International Symposium on Biomedical Imaging (ISBI) 2016
DOI: 10.1109/isbi.2016.7493463
|View full text |Cite
|
Sign up to set email alerts
|

Robust registration of calcium images by learned contrast synthesis

Abstract: Multi-modal image registration is a challenging task that is vital to fuse complementary signals for subsequent analyses. Despite much research into cost functions addressing this challenge, there exist cases in which these are ineffective. In this work, we show that (1) this is true for the registration of in-vivo Drosophila brain volumes visualizing genetically encoded calcium indicators to an nc82 atlas and (2) that machine learning based contrast synthesis can yield improvements. More specifically, the num… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
135
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 153 publications
(135 citation statements)
references
References 14 publications
0
135
0
Order By: Relevance
“…Correspondence of individual neurons or functional reference atlas regions across imaging modalities was achieved with landmark-based 3-D thin-plate spline warping of each fluorescence dataset to the ssEM dataset using BigWarp 49 .…”
Section: Methodsmentioning
confidence: 99%
“…Correspondence of individual neurons or functional reference atlas regions across imaging modalities was achieved with landmark-based 3-D thin-plate spline warping of each fluorescence dataset to the ssEM dataset using BigWarp 49 .…”
Section: Methodsmentioning
confidence: 99%
“…In addition, eYFP fluorescence from ChR2-EYFP contributes to the v3D signal ( Figure 4A). We therefore used a semi-manual landmark-based method to align brain volumes (Bogovic et al, 2016). Point correspondences between the v3D and AAT were manually determined.…”
Section: Three-dimensional Templatesmentioning
confidence: 99%
“…We used a landmark-based registration package (BigWarp in ImageJ (Bogovic et al, 2016)) in which corresponding landmarks can be identified in two image stacks. The warping algorithm uses a thin plate spline for interpolation between landmarks (Duchon, 1977).…”
Section: Brain Registrationmentioning
confidence: 99%
“…Software solutions are being developed, in the form of software that aids visualisation and alignment of large 3D image data, including the FIJI plugins TrakEM2 [49], BigDataViewer [50] and BigWarp [51], and ec-CLEM [52] on the ICY platform. These algorithms depend on manual identification of matching landmarks within the datasets for alignment, and can only work to an accuracy that is determined by the extent of the sample distortions caused by intermediate sample preparation steps.…”
Section: Correlative Microscopy Of Volumesmentioning
confidence: 99%